(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Mechatronics is a multidisciplinary branch that combines electronics, mechanics, and computer science. Due to the digital revolution, mechatronics is growing fast, rapidly spreading from manufacturing to many new sectors such as agriculture, healthcare, security, and transportation. As a consequence, mechatronics training courses are proliferating at the undergraduate and graduate levels. Nowadays, a considerable number of educational institutions, both academic and vocational, are offering mechatronics education, however their programs are not homogeneous and depend on teaching staff competence and available resources. This paper presents NewMetro, an EU funded project that aims to develop an innovative European framework of competences for mechatronics education and an educational model able to address the needs of young people as well as adult workers undergoing requalification programs. The philosophy of the project and the first activities carried out are illustrated and discussed.